Multiplex PCR Assay for Direct Identification of Group B Streptococcal Alpha-Protein-Like Protein Genes - Creti, Roberta (American Society for Microbiology, 2004)
We developed a group B streptococcus multiplex PCR assay which allows, by direct analysis of the amplicon size, determination of the surface protein antigen genes of alpha-C protein, epsilon protein, Rib, Alp2, Alp3, and Alp4. The multiplex PCR assay offers a rapid and simple method of subtyping Streptococcus agalactiae based on surface protein genes.